Male-mediated gene flow in patrilocal primates. - Grit Schubert; Colin J Stoneking; Mimi Arandjelovic; Christophe Boesch; Nadin Eckhardt; Gottfried Hohmann; Kevin Langergraber; Dieter Lukas; Linda Vigilant (PLoS ONE, 2011)
BACKGROUND: Many group-living species display strong sex biases in dispersal tendencies. However, gene flow mediated by apparently philopatric sex may still occur and potentially alters population structure. In our closest living evolutionary relatives, dispersal of adult males seems to be precluded by high levels of territoriality between males of different groups in chimpanzees, and has only been observed once in bonobos. Still, male-mediated gene flow might occur through rare events such as extra-group matings leading to extra-group paternity (EGP) and female secondary dispersal with offspring, but the extent of this gene flow has not yet been assessed. METHODOLOGY/PRINCIPAL FINDINGS: Using autosomal microsatellite genotyping of samples from multiple groups of wild western chimpanzees (Pan troglodytes verus) and bonobos (Pan paniscus), we found low genetic differentiation among groups for both males and females. Characterization of Y-chromosome microsatellites revealed levels of genetic differentiation between groups in bonobos almost as high as those reported previously in eastern chimpanzees, but lower levels of differentiation in western chimpanzees. By using simulations to evaluate the patterns of Y-chromosomal variation expected under realistic assumptions of group size, mutation rate and reproductive skew, we demonstrate that the observed presence of multiple and highly divergent Y-haplotypes within western chimpanzee and bonobo groups is best explained by successful male-mediated gene flow. CONCLUSIONS/SIGNIFICANCE: The similarity of inferred rates of male-mediated gene flow and published rates of EGP in western chimpanzees suggests this is the most likely mechanism of male-mediated gene flow in this subspecies. In bonobos more data are needed to refine the estimated rate of gene flow. Our findings suggest that dispersal patterns in these closely related species, and particularly for the chimpanzee subspecies, are more variable than previously appreciated. This is consistent with growing recognition of extensive behavioral variation in chimpanzees and bonobos.